Body of Intelligence: A Response to Jennifer Herdt - Harris, Harriet A. (Studies in Christian ethics, 2022)
This response to Jennifer Herdt’s paper, ‘Partisan Epistemology and Post-Truth Power’, looks to embodied intelligence for help in discerning integrity and truthfulness.